An Insight Review on Bloom Filter and Its Variants with Applications: An Emerging Hash Based Membership Querying Technique. (4th May 2015) - Saravanan, K.; Senthilkumar, A.
Abstract: Bloom filter idea was bloomed in the early seventy's as an efficient data structure tool for intelligent dictionary and spell check purposes and later revisited by the research community for its dynamic membership decision making and querying ability. Recently various optimization models for diverse applications emerged. Bloom filters are now implied in various networking applications, security applications and other emerging areas which require intensive querying and compact storage. Still it has scope for optimization and utilization. In this paper we present an insight survey on bloom filter and its variants and also discuss the applications and issues. This review will highly benefit the research community working in this field.